Virulence estimation by calculation of relative expression of NESTIN in different grades of astrocytoma from different age groups of Iraqi patients, extracted from brain tumor stem cells - saadoon, zainab zahid; Al-Khateeb, Huda M.; Alkhafaji, Khitam R. (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Astrocytoma, is heterogeneous tumor of the nervous system and studies on the virulence of these tumors reveal that their behavior is led by small population of cells which are the brain tumor stem cells (BTSCs) that drive the continuous proliferation and self-renewal. From the many markers that annotate BTSCs, are the CD133, and NESTIN. Objectives: Using CD133, to immunolabel BTSCs niches in paraffin sections of astrocytoma then, extraction of these cells, to calculate fold expression of NESTIN gene across the grades by real time PCR. Materials and methods: Paraffin blocks of four grades of primary astrocytoma have been selected from three age groups from Iraqi patients. The age groups were stratified into: children (0-17years) adults (18-49years) and older (50-80years). The samples were stained with CD133, then positive areas were extracted to perform relative expression of NESTIN gene by real time PCR Results: The expression of NESTIN for all grades, increased by tens of folds in relation to calibrator then this fold expression increased dramatically in an ascending manner with increasing of the grade in the same group. The fold expression of NESTIN gene in all grades was the highest in the adulthood (18-49) years group. Conclusion: Relative expression of NESTIN gene of BTSCs in different grades of astrocytoma can be a useful tool for the assessment of the virulence with ascending the grades. This expression was the highest at age (18-49) years.